Pichia pastoris: SEL RAGI UNTUK PRODUKSI PROTEIN REKOMBINAN - Neng Herawati; Arizah Kusumawati; Adi Santoso (Research Center for Biology-Indonesian Institute of Sciences, 2018)
Pichia pastoris is a group of methylotropic yeast known as a host of expression and protein production which is widely used for biopharmaceutical-based drug production. This yeast can grow fast with a high cell density. Its genetic stability, high cell density, and stress resistance make the development process and scale-up of P. pastoris can increase to a scale of 200,000 liters of culture. In contrast to the expensive and complex development of recombinant protein production in mammalian cells, the development of production in P. pastoris is relatively simple and cheaper. The advantage of P. pastoris as an expression system is that it is able to use methanol as a carbon source by inducing the expression of alcohol oxidase oxidase (AOX) enzyme. Promoter used by this enzyme is also used as a strong promoter for the expression of proteins that we want. Unlike in bacterial and mammalian systems, recombinant protein production in Pichia cells is not contaminated with endotoxins or viruses so it is safer and simplifies the downstream processes in bioproduction. The level of endogenous protein in the low supernatant allows Pichia to cultivate with a high volumetric productivity, therefore the process of protein production becomes very economical. This review provides an overview of several things that must be considered in utilizing P. pastoris as an expression system including the selection of vectors, strains, vector integration mechanisms into the genome, glycosylation processes, and applications in industry.